Model‐Based System Patterns for Automated Ground Vehicle Platforms. (28th October 2015) - Peterson, Troy; Schindel, William D.
Abstract: Automated Ground Vehicle (AGV) platform research and engineering is proliferating across commercial, military, and consumer applications. Beyond diversity of form and application, AGVs can be manned or unmanned, and exhibit a broad range of automated control, from partial to full autonomy, making these vehicles strikingly diverse. This paper reports on application of Pattern‐Based Systems Engineering (PBSE) to representation of automated ground vehicle platforms. PBSE is based upon reusable, configurable S*Models conforming to the S*Metamodel, expressed in any modeling language and toolset. The INCOSE MBSE Initiative Patterns Challenge Team has been practicing PBSE across applications, reported in this and other IS2015 papers. A specialized class of Cyber‐Physical Systems, AGVs are subject to intense interest, creating new opportunities, risks, and complexities. To address the diversity and complexity of these systems, the Embedded Intelligence (EI) Pattern, another S*Pattern, is being applied by the team to illustrate its applicability to an AGV Platform Pattern.